ilmu rasm al quran - Shoim, Mohammad shoim maulidi Mohamad shoim maulidi (Maliki Interdisciplinary Journal, 2024)
the science of rasm al-Quran is the science that studies the writing of mushaf al-Quran using special methods, both in writing the pronunciations and the letter shapes used, the writing of the Koran during the time of the Prophet was carried out by his companions both in terms of writing and order with the aim of gathering Muslims in one mushaf by equating the reading while uniting the arrangement of the verses sequentially, the aim being to avoid misunderstandings or differences in understanding between one mushaf and another